Genetic relatedness in extended-spectrum beta-lactamase-producing Escherichia coli from clinical isolates using enterobacterial repetitive intergenic consensus polymerase chain reaction - Tanko, Nuhu; Tolulope, Olayinka Adebola; Olajumoke, Bolaji Rebecca; Ong, Eugene Boon Beng; Yahaya, Mohammed; Olalekan, Olayinka Busayo (International Journal of Health Sciences, 2021)
Objectives: The aim of this study is to determine the genetic relatedness of extended-spectrum beta-lactamases (ESBL)-producing Escherichia coli using the enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) technique. Methods: Suspected Gram-negative bacteria with their identities from the clinical samples were confirmed using Microgen GN-A-ID Kit. The double-disc synergy test was used to confirm for ESBL-producing E. coli. The susceptibility of the organisms was tested against eleven antimicrobial agents. A singleplex PCR assay was carried out targeting TEM, SHV, CTX-M, and OXA. ERIC-PCR performed, and band patterns obtained were visually evaluated. A dendrogram of the ERIC-PCR fingerprint pattern was done with the aid of DendroUPGMA using the cluster method. Results: Of the 576 clinical samples collected, 23 isolates were confirmed E. coli, and all (100%) are ESBL producers. The highest antibiotic resistance rate was recorded in cefixime (95.6%), and the least was amikacin (17.4%). The predominant ESBL gene is blaTEM genes (95.6%). Gel analysis of ERIC-PCR revealed 1–6 bands. The profiles of the ERIC-PCR differentiated the 23 E. coli isolates into four ERIC cluster types. Conclusion: More than 80% of the isolates are sensitive to amikacin, with greater than 95% harboring blaTEM genes. Overall, ERIC obtained from the clinical specimens indicated some evidence in the genetic relatedness of the ESBL genes among E. coli isolates.